Impact of green revolution on rice cultivation practices and production system: A case study in Sindang Hamlet, Rancakalong Village, Sumedang District, West Java, Indonesia - RAHMI AULIA HIDAYAT; JOHAN ISKANDAR; BUDHI GUNAWAN; Ruhyat Partasasmita (Society for Indonesian Biodiversity, 2020)
Abstract. Hidayat RA, Iskandar J, Gunawan B, Partasasmita R. 2020. Impact of green revolution on rice cultivation practices and production system: A case study in Sindang Hamlet, Rancakalong Village, Sumedang District, West Java, Indonesia. Biodiversitas 21: 1258-1265. In the past, farmers of Sindang Hamlet, Rancakalong Village, West Java practiced the wet-rice (sawah) farming system based on the Traditional Ecological Knowledge (TEK) and belief system. They coordinate their planting schedule according to indigenous calendar known as kalender tani or pranata mangsa (Javanese). The various inputs of the sawah farming system, namely rice seeds, organic fertilizers, and pesticides intensively used originate from the village, made little use of farm supplies obtained through purchased from outside (market). In the early 1970s, the Government of the Republic of Indonesia introduced the Green Revolution to increase the rice production of the wet-rice farming system. The five-farming effort (panca usaha tani) programs, namely the use of the High Yielding Rice Varieties (HYVs), the provision for inorganic chemical fertilizers, the use of synthetic pesticides, the development and improvement of irrigation, and the improvement of methods of rice planting methods were intensively implemented. About ten years later, in 1980s, the sawah farmers of Rancakalong Village, Sumedang District, West Java have adopted the Green Revolution program. As a result, the traditional the wet-rice cultivation practices of Rancakalong farmers that was originally based on the low-external inputs has dramatically changed to the high-external-input agriculture, depending more on artificial inputs, such as inorganic fertilizers, pesticides, fossil energy, and modern rice seeds, which originate from outside of the village and generally have to be purchased. The aim of this study is to document and analyze the changing cultivation practices of the wet-rice farming systems, and rice production systems. Study was undertaken in Sindang Hamlet, Rancakalong Village, Sumedang District, West Java. Method applied in this study was a mixed-method, combination of qualitative and quantitative techniques, including observation, semi-structured interviews, and structured interviews applied to 64 respondents. The result of the study showed that the farmers have stopped their traditional cyclical planting schedule based on kalender tani, most local rice varieties have been replaced by the superior or High Yielding Rice Varieties (HYVs), and farmers have become dependent on external inputs, namely inorganic fertilizers, synthetic fertilizers, modern rice seeds, and fossil energy. Consequently, the HYVs have also more vulnerable to diseases and pests, such as brown plant-hopper (Nilarparvata lugens Stal), and also vulnerable to scarcity of water due to drought caused by climate change. This study stresses that a model agriculture system that is ecologically sound, economically viable, and adaptable must be undertaken to develop sustainable agriculture.